Role of translocator protein density, a marker of neuroinflammation, in the brain during major depressive episodes - Setiawan, Elaine; Wilson, Alan A; Mizrahi, Romina; Rusjan, Pablo M; Miler, Laura; Rajkowska, Grazyna; Suridjan, Ivonne; Kennedy, James L; Rekkas, P Vivien; Houle, Sylvain; Meyer, Jeffrey H (JAMA psychiatry (Chicago, Ill.), 2015)
The neuroinflammatory hypothesis of major depressive disorder is supported by several main findings. First, in humans and animals, activation of the immune system causes sickness behaviors that present during a major depressive episode (MDE), such as low mood, anhedonia, anorexia, and weight loss. Second, peripheral markers of inflammation are frequently reported in major depressive disorder. Third, neuroinflammatory illnesses are associated with high rates of MDEs. However, a fundamental limitation of the neuroinflammatory hypothesis is a paucity of evidence of brain inflammation during MDE. Translocator protein density measured by distribution volume (TSPO VT) is increased in activated microglia, an important aspect of neuroinflammation. To determine whether TSPO VT is elevated in the prefrontal cortex, anterior cingulate cortex (ACC), and insula in patients with MDE secondary to major depressive disorder. Case-control study in a tertiary care psychiatric hospital from May 1, 2010, through February 1, 2014. Twenty patients with MDE secondary to major depressive disorder and 20 healthy control participants underwent positron emission tomography with fluorine F 18-labeled N-(2-(2-fluoroethoxy)benzyl)-N-(4-phenoxypyridin-3-yl)acetamide ([18F]FEPPA). Patients with MDE were medication free for at least 6 weeks. All participants were otherwise healthy and nonsmokers. Values of TSPO VT in the prefrontal cortex, ACC, and insula. In MDE, TSPO VT was significantly elevated in all brain regions examined (multivariate analysis of variance, F15,23 = 4.5 [P = .001]). The magnitude of TSPO VT elevation was 26% in the prefrontal cortex (mean [SD] TSPO VT, 12.5 [3.6] in patients with MDE and 10.0 [2.4] in controls), 32% in the ACC (mean [SD] TSPO VT, 12.3 [3.5] in patients with MDE and 9.3 [2.2] in controls), and 33% in the insula (mean [SD] TSPO VT, 12.9 [3.7] in patients with MDE and 9.7 [2.3] in controls). In MDE, greater TSPO VT in the ACC correlated with greater depression severity (r = 0.63 [P = .005]). This finding provides the most compelling evidence to date of brain inflammation, and more specifically microglial activation, in MDE. This finding is important for improving treatment because it implies that therapeutics that reduce microglial activation should be promising for MDE. The correlation between higher ACC TSPO VT and the severity of MDE is consistent with the concept that neuroinflammation in specific regions may contribute to sickness behaviors that overlap with the symptoms of MDE.